Prototype of a mobile application for the detection of car accidents on the roads of Peru - Meneses Claudio, Brian Andreé (2023)
According to studies of the World Health Organization at least around 1. 35 million deaths and between 20 to 50 million injuries are caused due to car accidents, due to this fact the present research work seeks to mitigate this figure before the problem of car accidents on the roads of Lima, that is why a mobile application was designed whose objective is to detect and report accidents, when performing this action the driver sends his contact information (ID, phone, email, family number) and location in real time to the nearby authorities such as police stations or hospitals and likewise the message comes as a notification to their families. For its development we used the agile methodology Scrum whose structure was very useful to display the information proposed, also design tools such as Balsamiq and Marvel App were used to create the interface. Finally, it is concluded that car accidents is a problem that negatively affects our society, also with the application it was possible to design an interactive application that will be very useful for drivers if it is ever implemented, on the other hand, this research seeks to encourage researchers to use technological means to improve the quality of life of people and thus continue to advance as a socie.